Modified Bogolyubov’s derivation of the two-fluid hydrodynamics - Shygorin, Pavlo P.; Svidzynskyi, Anatolii V.; Шигорін, Павло Павлович; Свідзинський, Анатолій Вадимович (Національна академія наук України, 2010)
A consistent microscopic derivation of the two-fluid hydrodynamics for the superfluid helium-4 in the ideal approximation is represented. The starting point in our formalism is a system of Heisenberg’s equation of motion for the both normal and anomalous correlation functions. We also use the mixed Wigner representation. It allows directly, very easy and with the rigorous mathematic perform a series expansion of the correlation functions equation of motion by the gradients. To finding of the hydrodynamic fluxes was constructed a local equilibrium statistical operator for superfluid helium in the frame of reference, where condensate is rest. У роботi представлено послiдовний мiкроскопiчний вивiд дворiдинної гiдродинамiки надплинного гелiю-4 в iдеальному наближеннi. Вiдправною точкою у нашому формалiзмi є система гайзенбергiвських рiвнянь руху для нормальної та аномальної кореляцiйних функцiй. Використання мiшаного представлення Вiгнера дозволяє легко i з математичною строгiстю виконати розклад рiвнянь руху для кореляцiйних функцiй за градiєнтами. Для обчислення гiдродинамiчних потокiв у роботi побудовано локально-рiвноважний статистичний оператор надплинної рiдини в системi вiдлiку, пов’язанiй з конденсатом.
Модифіковане Боголюбовське виведення дворідинної гідродинаміки